IMPLEMENTASI PENDEKATAN DEEP LEARNING PADA MATA PELAJARAN IPAS DI SEKOLAH DASAR (STUDI KASUS SD 13/1 MUARA BULIAN) - Rivaldi Aulia Fikri; Sofwan, Muhammad; Alirmansyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The learning of Science and Social Studies (IPAS) in elementary schools is expected to foster meaningful understanding, critical thinking, and the ability to connect concepts with real-life contexts. However, learning practices are often still oriented toward surface learning, causing students to have difficulty developing deep conceptual understanding. This study aims to describe the implementation of the deep learning approach in IPAS learning at SD 13/1 Muara Bulian, as well as to identify students’ responses and supporting and inhibiting factors in its application. This research employed a qualitative approach with a case study design. Data were collected through classroom observations, interviews with teachers and students, and documentation analysis. The results show that the implementation of the deep learning approach in IPAS learning was carried out through contextual learning activities, active student engagement, collaborative discussions, and reflective learning processes. The approach encouraged students to better understand concepts, relate learning materials to daily life, and demonstrate higher learning engagement. Supporting factors included teacher readiness and learning environment, while inhibiting factors involved limited time and varying student learning abilities. Overall, the deep learning approach contributed positively to improving the quality of IPAS learning in elementary school.